Spiritually Based Classroom Management as a Strategy For Improving Learning Quality Amid the Challenges of Modernity in Islamic Education - Tumiran, Tumiran; Ependi, Rustam; Abrianto, Danny; Sitorus, Panca Abdini (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
The challenges of modernity have eroded spiritual values in Islamic education, so a classroom management strategy is needed that balances academic achievement and religious character building. This research examines religious classroom management innovations in improving the quality of student learning at Madrasah Aliyah Swasta Tarbiyah Islamiyah. The focus is on the school's innovative strategies in creating a religious learning atmosphere, conducive, and supportive of students' character and academic development. The research method uses a phenomenological qualitative approach with observation, interview, and documentation techniques. The results show that spiritual-based classroom management through the integration of Islamic values, worship habits, and strengthening the spiritual relationship between teachers and students can create a positive and meaningful learning environment. This strategy has an impact on improving discipline, learning motivation, and academic achievement. The findings corroborate Vygotsky's social constructivism theory that emphasizes the importance of social and cultural interactions in learning, as well as Islamic education theory that places spirituality at the core of forming a whole person.